2020
DOI: 10.1093/jat/bkaa036
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Organochlorine Pesticides in Human Tissues Assessed Using a Microextraction Procedure and Gas Chromatography–Mass Spectrometry

Abstract: This work focuses on the development, validation and application of an analytical method for the determination of twenty organochlorine pesticides (OCPs) in human tissues using salting-out liquid–liquid extraction and dispersive liquid–liquid microextraction for sample preparation and gas chromatography–mass spectrometry to analyze the obtained extracts. Measurement of the concentration levels of these toxics in tissues can be used to assess the risk of the population to exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…OCPs have been extracted from sediment using the soxhlet method [ [37] , [38] , [39] ]. Isotope dilution and centrifugation [ 40 , 41 ] and SPE [ 42 , 43 ] have been utilized for human serum extraction, while salting-out liquid-liquid extraction (SALLE) combined with dispersive liquid-liquid microextraction (DLLME) has been reported for human tissue (liver, kidney, brain, etc) [ 44 ].…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…OCPs have been extracted from sediment using the soxhlet method [ [37] , [38] , [39] ]. Isotope dilution and centrifugation [ 40 , 41 ] and SPE [ 42 , 43 ] have been utilized for human serum extraction, while salting-out liquid-liquid extraction (SALLE) combined with dispersive liquid-liquid microextraction (DLLME) has been reported for human tissue (liver, kidney, brain, etc) [ 44 ].…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“…The carrier gas was helium (purity 99.99 %) with a flow rate of 1 Ml/min. RT: 15.27–22.29 min” [ 404 ] Plasma/serum 23 0.001–0.029 0.002–0.093 85.9–109 1.97–19.6 GC-MS/MS: “The oven temperature program was started at 70 °C, increased to 240 °C at 20 °C/min, and continuously increased to 310 °C at 8 °C/min and maintained at the final temperature for 11 min” [ 405 ] Plasma/serum 7) 0.02–0.07 4–40 GC-MS/MS: “The GC oven program was set to following values: 115 °C (2 min), 4 °C/min, 260 °C (1 min), 30 °C/min, 320 °C (2 min)” [ 406 ] serum 26 7 × 10 −5 -0.01344 30–124 HRMS/HRMS [ 407 ] Blood serum 11 74–120 <20 GC-MS/MS, UHPLC–MS/MS [ 101 ] Human tissue (liver, kidney, heart, spleen, lung, brain and abdominal fat) 20 1.0–16 85–109 <12 GTC-MS: “Splitless, the GC oven program started with an isothermal stage at 100 °C for 0.5 min, increasing at 10 °C/min ∼180 °C, and then at 2 °C/min ∼225 °C (2 min), to finally reach 265 °C at a rate of 20 °C/min, which was maintained for 1 min” [ 44 ] Human blood 8 0.004; 5 × 10 −5 ng a for detector Ave: 95 GC-ECD [ 408 ] ...…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“…Since 1970, OCPs have been withdrawn from use, but due to their persistence in the environment, semi volatility, low solubility in water, toxicity, and lipophilicity, these residues can still be found in environmental samples and food (Ferronato et al 2018 ; Huang et al 2017 ). Exposure to organochlorines occurs generally via respiratory tract, skin absorption, or eating contaminated fish, milk, eggs and meat (Pastor Belda et al 2021 ). Epidemiological and animal studies have shown a negative impact of organochlorine pesticides on reproductive and immune system, endocrine disruption as well as dysregulation lipid metabolism (Martyniuk et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its excessive harm, the use of organochlorine was banned in 2004. Although these OCPs have been banned, they may still remain in water samples [10], soils [11], sediments [12], aquatic organisms [13], and human bodies [14,15] due to their high persistence. Therefore, there is an urgent need to establish a sensitive and accurate analytical method to monitor OCP residues in the ecological environment, which is of great significance for human development.…”
Section: Introductionmentioning
confidence: 99%